2005
DOI: 10.1016/j.marpolbul.2005.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of trace elements in marine fish and its risk assessment in Malaysia

Abstract: Concentrations of trace elements (V, Cr, Mn, Co, Cu, Zn, Ga, Se, Rb, Sr, Mo, Ag, Cd, Sn, Sb, Cs, Ba, Hg, Tl, Pb and Bi) were determined in muscle and liver of 12 species of marine fish collected from coastal areas in Malaysia. Levels of V, Cr, Mn, Co, Cu, Zn, Ga, Sr, Mo, Ag, Cd, Sn, Ba and Pb in liver were higher than those in muscle, whereas Rb and Cs concentrations showed the opposite trend. Positive correlations between concentrations in liver and muscle were observed for all the trace elements except Cu an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
98
3
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 143 publications
(118 citation statements)
references
References 17 publications
16
98
3
1
Order By: Relevance
“…Another study conducted in the Straits of Malacca reported that the range of Cd mean concentration was from 0.006 to 0.03 mg/kg (Alina et al 2012). Based on the findings of this study, it was observed that the level of Cd in fish increased compared with the study done by Agusa et al (2005). This could be an indicator of the pollution status in coastal water of Port Dickson.…”
Section: Estimation Of Potential Health Risk Assessmentsupporting
confidence: 51%
See 4 more Smart Citations
“…Another study conducted in the Straits of Malacca reported that the range of Cd mean concentration was from 0.006 to 0.03 mg/kg (Alina et al 2012). Based on the findings of this study, it was observed that the level of Cd in fish increased compared with the study done by Agusa et al (2005). This could be an indicator of the pollution status in coastal water of Port Dickson.…”
Section: Estimation Of Potential Health Risk Assessmentsupporting
confidence: 51%
“…There are limited local studies performed to determine the Cr concentration in local marine fish in Malaysia. A study by Agusa et al (2005) reported that Cr level in fish from coastal water of Port Dickson was within the range 0.31 and 0.71 mg/kg. The findings from present study also showed an increment in Cr levels in fish samples from coastal water of Port Dickson.…”
Section: Estimation Of Potential Health Risk Assessmentmentioning
confidence: 99%
See 3 more Smart Citations